Tindak Pidana Penadahan Dalam Kegiatan Usaha Pertambangan Mineral Bukan Logam Dan Batuan Tanpa Izin - I Made Sadhu Arta Kori; I Nyoman Gede Sugiarta; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2024)
In Indonesia, there is a strong and steady development of roads, buildings and public facilities that will be very useful for the community in the future. However, in mineral exploitation activities there are still people who violate these regulations by committing criminal detention. The formulation of the problem is:1) how is the licensing arrangement for rock and nonmetal mineral mining companies? 2) What are the administrative sanctions for arresting entrepreneurs who carry out exploitation of non-metal minerals and rocks? This researchs uses normative legal research methods using legislation and document research methods by analysing and examining current legal regulations as a basis for problem solving. The results show that legal provisions related to criminal sanctions against licences to own and cultivate non-metal minerals and rocks are implied in the Criminal Code and regulated in Law Number 3 of 2020, amending and adding a number of articles in Law Number 4 of 2020. 2009, Articles 158 and 160 related to Non-Metal and Stone Mining, Government Regulation Number 5 of 2021 concerning the Implementation of Business Licences. In this case, there are sanctions and fines if business entities commit preventive violations in the exploitation of non-metal minerals and rocks.